The Aplication Effect Of Liquid Fertilizer to Maja Fruit fermentation and NUPOC with Hydroponic Styrofoam Method (Floating Raft) to the Ipomoea aquatica Plant Growth - Laili, Saimul (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of this study was to determine the effect of liquid organic fertilizer fermented by maja fruit and NUPOC on the growth of water spinach plants and to determine the effective concentration affecting the growth of water spinach plants (Ipomoea aquatica). This research was carried out by CV. Javacola which is located on Jalan Joyo Suryo Lowokwaru Malang, during October to December 2021. Using the Experimental Randomized Block Design (RAK) method. In each nutrient, there were 9 treatments and 5 replications, with treatment concentrations of 5 ml/liter, 10 ml/liter, 15 ml/liter and 20 ml/liter. Data analysis used the one-way ANOVA test and if there was a significant difference, it was continued with the 5% BNT test. The results showed that the treatment that had the highest effect on plant height, number of leaves, root length, number of roots, wet weight and dry weight was P1A4 treatment (Maja fruit fermentation 20 ml/liter), while the NUPOC treatment had a high effect on growth, namely in the P2A3 treatment (NUPOC 15ml/liter). Existing limiting factors such as temperature, humidity, light intensity and soil pH are still within the range of water spinach plant growing requirements.